Challenges and Opportunities of Special Needs Teachers in Inclusive Schools: A Thematic Qualitative Study on Teachers' Psychological Well-Being - Anggreany, Yuliana; Sugianto, Dicky; Sitepu, Yenika Mariani; Cristabelle, Eleanora (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2025)
This research explores the challenges and opportunities experienced by teachers of students with special needs (TSSN) in inclusive schools, as well as the impact on their psychological well-being (stress and relationship with others). Students with special needs (SSN) possess the same right to education as their peers without special needs, and the implementation of inclusive education in Indonesia places teachers at the forefront of addressing student diversity. The research employed a descriptive qualitative method with thematic analysis of data obtained from open-ended online questionnaires completed by 58 inclusive school teachers (81% female, mean age 36.38 years, with varying teaching experience). The findings indicate that the primary challenges faced by teachers include a lack of in-depth understanding of TSSNs, inadequate facilities, difficulties in managing learning and classroom dynamics, and the need to respond to a wide range of student behaviors and emotions. Nevertheless, teachers also identified opportunities to improve their competencies and build meaningful relationships with students. The discussion highlights the necessity for more comprehensive support from schools and the government, encompassing training, adequate facilities, adaptive curricula, and professional support teams. In conclusion, this research highlights the importance of psychological interventions and systemic support to improve the well-being of inclusive school teachers, which will ultimately positively impact the quality of education for SSNs. This finding is useful for designing school-based interventions and public policies that support the well-being of inclusive education teachers.